Incidence of Colorectal Cancer in Saiful Anwar Hospital, Malang January 2010- April 2015 - Lia Sasmithae; Syifa Mustika (The Indonesian Society for Digestive Endoscopy, 2017)
Background: Colorectal carcinoma is the third most common malignancy worldwide and the second most frequently found cause of mortality in the United States. In Indonesia, the number of colorectal cancer patients ranks 10th (2.75%) after other cancers (cervical, breast, lymph nodes, skin, nasopharyngeal, ovarium, soft tissue, and thyroid). The main key to success in managing this carcinoma is by detecting the cancer in early stage to enable curative treatment to be performed. But, unfortunately most patients in Indonesia seek for treatment in the advanced stage, causing low survival rate. Colorectal carcinoma requires multimodalities management and there is no uniformity of management approach in the national level. This study was aimed to identify the incidence, epidemiology, and risk factors which influence the occurrence of colon and rectal cancer in Saiful Anwar Hospital (SAH), Malang based on colonoscopy examination from January 2010-April 2015.Method: Descriptive study, with total sampling method. Samples were colon and rectal cancer patients in SAH, Malang who underwent colonoscopy within January 2010 – April 2015.Results: We found 472 eligible samples, which comprised of 50 individuals (11%) with the age of less than 36 years old, 326 individuals (69%) in middle aged group with the age of 36-65 years old, 96 individuals (20%) in older aged group with the age of more than 65 years old. Patients were predominantly male with 248 individuals (53%), while female patients were 224 individuals (47%). The most common location of the tumour was in the rectum, which was found in 380 individuals (74.15%). The most common clinical symptoms was bloody stool with mucus. From patients in this study, 87 individuals (18.43%) had history of smoking, 11 individuals (2.3%) had family history of cancer, and 58 individuals (12.28%) consumed traditional herbal drinks (jamu). Patients’ characteristics of colon cancer based on anatomical pathology results showed that the most common was moderately differentiated adenocarcinoma in 33 patients (61.11%), followed by well-differentiated adenocarcinoma in 14 patients (25.93%), and the least common was those with anatomical pathology results revealing unspecific adenocarcinoma in 7 patients (12.96%). Characteristics of patients with rectal cancer based on anatomical pathology results showed that the most commonly found was moderately differentiated adenocarcinoma in 72 patients (54.15%), well-differentiated adenocarcinoma in 34 patients (25.56%), unspecific adenocarcinoma in 24 patients (18.04%) and the least common was those with anatomical pathology results of mucinous adenocarcinoma found in 3 patients (2.25%).Conclusion: The conclusion of this study was colon and rectal cancer were frequently found in middle aged group. The most common location was rectum. Mainly found in male compared to female.